Strategi Penilaian Kinerja Guru di Masa Pandemi Studi Kasus di MA Midanutta'lim - Turrahman, Akbar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In order to achieve the common goal of maintaining the country's stability from pandemics both in the economic and educational, there needs to be a slight change in strategy in the management of education. The purpose of this study was to know the strategic assessment of teachers performance in pandemic era, this study uses case study research methods. In this study produces several forms the performance assessment process, including the first stage of analyzing the situation and opinions from several sources related to teacher performance in a certain period, then conducting assessment activities on teacher performance that are closed with an evaluation of the results of activities that have been done to improve teacher performance by conveying back to the teacher.